2016
DOI: 10.4103/2321-1407.173726
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of stress patterns on maxillary posterior segment when intruded with mini implant anchorage: A three-dimensional finite element study

Abstract: Introduction The aim of this study is to evaluate stress and displacement effects of maxillary posterior intrusion mechanics with mini-implant anchorage by using finite element method. Materials and Methods A computer stimulation of three-dimensional model maxilla with all teeth, PDL, bone, mini-implants, brackets, arch wire, force element, and transpalatal arch was constructed on the basis of average anatomic morphology. Finite element analysis was done to evaluate the amount of stress and its distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…10,15 Pekhale et al evaluated the stress patterns on the posterior maxillary segment after intrusion with the help of mini-implants by applying a force of 300 grams to each dental segment and found 17.019 N/mm 2 of Von Mises stress on the buccal surface of the crown of maxillary first molar. 4 In the present study maximum tensile stress was observed at lingual aspect and was around 5.4MPa while as compressive stress was observed at the cervical region and was around 2.28 MPa (Figures 2, 3, 4 and 5). Maximum Von Mises stress was observed at lingual aspect and was around 8.49MPa which is more than the values recorded by Dawer et al 10 A force of 100 gram/cm 2 (0.01N/mm 2 ) was suggested by Bench et al as the ideal stress for the periodontal ligament which maintains the vascularity and prevents hyalinization.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…10,15 Pekhale et al evaluated the stress patterns on the posterior maxillary segment after intrusion with the help of mini-implants by applying a force of 300 grams to each dental segment and found 17.019 N/mm 2 of Von Mises stress on the buccal surface of the crown of maxillary first molar. 4 In the present study maximum tensile stress was observed at lingual aspect and was around 5.4MPa while as compressive stress was observed at the cervical region and was around 2.28 MPa (Figures 2, 3, 4 and 5). Maximum Von Mises stress was observed at lingual aspect and was around 8.49MPa which is more than the values recorded by Dawer et al 10 A force of 100 gram/cm 2 (0.01N/mm 2 ) was suggested by Bench et al as the ideal stress for the periodontal ligament which maintains the vascularity and prevents hyalinization.…”
Section: Discussionsupporting
confidence: 62%
“…288332 elements and 64771 nodes were used and the material properties assigned to the various parts were acquired from an existing study. 4 (Table 1). The boundary conditions were defined by constraining the top portion of the maxillary bone in all directions so that there would be no displacement or stress in that area.…”
Section: Methodsmentioning
confidence: 99%
“…It allows one to evaluate complex stress distributions and displacement patterns on the facial skeleton model [29]. Interpretation of the results of the analysis should be made carefully and prudently, because it is a skeletal model created on the basis of a 3D computed tomography reconstruction of the facial skeleton with material properties assigned according to Pekhale et al [22].…”
Section: Discussionmentioning
confidence: 99%
“…® ), where a resulting volumetric mesh of 10 nodal tetrahedrons of the second order was created. The finite element mesh was imported into the ANSYS 15.0 (Swanson Analysis System of USA) software, where material properties were assigned according to Pekhale et al (Table 1), boundary conditions were determined and calculations using the finite element analysis were performed [22]. The result is a dense mesh of higher order finite elements ensuring accurate mapping of the stress distribution and displacement field.…”
Section: Construction Of the Facial Skeleton Model For The Finite Element Analysismentioning
confidence: 99%
“…Besides, it has been reported that force application from counterbalancing sites lead to a more balanced intrusion than using transpalatal arch, and that root surface areas of the anchor tooth has to be considered [23]. Similarly, force applications from the buccal and palatal sides, and using a transpalatal arch with sufficient resistance could be advised in order to prevent buccal tipping during posterior intrusion [37].…”
Section: Discussionmentioning
confidence: 99%